ANALISIS PENGARUH KUALITAS PELAYANAN SUB BAGIAN AKADEMIK TERHADAP LOYALITAS MAHASISWA DI FEB UNDIP SEMARANG - Adhi Widyakto; Dian Triyani; Rr. Lulus Prapti N.S.S (Universitas Semarang, 2021)
This study aims to determine the quality of academic service on student loyality. The object of this research at the FEB Undip. The independent variables in this study are tangibles, responsiveness, reliability. The dependent variable in this study is student luck at the Faculty of Economics and Businees at Diponegoro University. The population in this research is 3575 active students with a sample of 150 students. The method used in this research is a probability sampling method with proportional stratified random sampling technique. This research uses Multiple Linear Regression Analysis tool.The results showed that the tangibles, responsiveness, reliability partially has a positive and significant effect on student satisfaction effect on student loyality at the Faculty of Economics and businees, University Diponegoro.Riset ini bemaksud guna mengenal bobot layanan sub bagian Akademik berkenaan loyalitas mahasiswa. Obyek pada riset ini di FEB Undip. Komponen independen pada riset ini adalah bukti nyata (tangibles), kemampuan reaksi (responsiveness), kehandalan (realibility). faktor dependen dalam riset ini ialah kepuasan mahasiswa FEB Undip. Jumlah populasi pada riset ini sebanyak 3575 mahasiswa aktif dengan sampel yang digunakan sejumlah 150 mahasiswa. Teknik yang dipakai dalam riset ini ialah metode probability sampling berdasarkan teknik proportional stratified random sampling. Riset ini memakai alat Analisis Regresi Linear Berganda. Kesimpulan Riset memperlihatkan kalau aspek bukti nyata (tangibles), kemampuan reaksi (responsiveness), kehandalan (realibility) secara parsial berdampak positif dan signifikan kepada kepuasan pelayanan berakibat kepada loyalitas mahasiswa di FEB Undip.